Reliability based assessment of reinforced concrete columns under eccenric loads using refined first-order reliability method - Hossein Shahraki; Ahmad Reyhani (Numerical Methods in Civil Engineering)
This paper presents an efficient approach for the failure probability assessment of reinforced concrete (RC) columns under the combination of the gravity and seismic loads considering uncertainty in the load eccentricity. In the proposed approach, Limit State Function (LSF) are conditionally formulated for the load eccentricity in column and the conditional reliability index is assessed using Refined First-Order Reliability Method (R-FORM) based on cross-entropy optimization method. The conditional reliability index along with the probability density function of the load eccentricity have been used to estimate the failure probability of the column. The important feature of the proposed approach is precise find of the most probable failure point, which provide a precise estimation of the failure probability of the RC columns under different load eccentricities. The results indicate that the failure probability of the RC columns is sensitive to uncertainty in the load eccentricity as well as of structural system, particularly when the load eccentricity is in the tension failure region. The effect of longitudinal reinforcement varies depending on the probability density function of the load eccentricity and the region of the interaction diagram where the column is loaded.